2020
DOI: 10.1186/s12933-020-01135-z
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-23 is associated with imaging markers of diabetic cardiomyopathy and anti-diabetic therapeutics

Abstract: Background The biomarker fibroblast growth factor-23 (FGF-23) has been associated with increased cardiovascular morbidity and mortality in both patients with and without type 2 diabetes. The aim of this study was to evaluate the relationship between FGF-23 and cardiac structure, function and perfusion in patients with type 2 diabetes and normal or mildly impaired kidney function. Furthermore, to investigate the association between FGF-23, anti-diabetes therapy and the classic complications and risk factors ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
2
15
0
2
Order By: Relevance
“…We also found that LVM was increased after the modeling of 1.5 months. Similar results were reported by Sorensen et al [ 18 , 19 ] in a large cohort of patients examined with CMR. In their entire cohort, Sorensen et al found that LVM was generally higher in these patients with FGF-23 above the median.…”
Section: Discussionsupporting
confidence: 91%
“…We also found that LVM was increased after the modeling of 1.5 months. Similar results were reported by Sorensen et al [ 18 , 19 ] in a large cohort of patients examined with CMR. In their entire cohort, Sorensen et al found that LVM was generally higher in these patients with FGF-23 above the median.…”
Section: Discussionsupporting
confidence: 91%
“…Mitochondria are remarkably dynamic organelles that perform diverse yet interconnected functions by producing ATP and multiple biosynthetic intermediates that participate in cellular stress responses, autophagy, and apoptosis ( Ma et al, 2020 ; Pflüger-Müller et al, 2020 ; Sawashita et al, 2020 ). The mitochondrial membrane potential is a key indicator of mitochondrial activity as it reflects the processes of electron transport and oxidative phosphorylation, which enable ATP production ( Schinner et al, 2020 ; Sørensen et al, 2020 ). High-glucose conditions have been shown to disrupt the mitochondrial membrane potential and increase the ATP levels ( Nesti et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study in 71 patients with T1DM and early DKD, FGF-23 levels correlated with diastolic cardiac dysfunction [ 82 ]. In a larger cross-sectional study in 246 patients with Τ2DM, increased serum levels of FGF-23 were also associated with cardiac diastolic dysfunction and with reduced myocardial perfusion reserve [ 83 ]. In another cross-sectional study in 545 African American patients with T2DM, FGF-23 concentrations were associated with the extent of coronary artery calcification [ 84 ].…”
Section: Fibroblast Growth Factor-23mentioning
confidence: 99%